Cпособ определения оптимальной скорости резания - Нестеренко В. П. Владимир Петрович; Бородин Ю. В. Юрий Викторович; Раков Ю. Я. Юрий Яковлевич; Галанов Ю. И. Юрий Иванович; Арефьев К. П. Константин Петрович
опубл. 27.11.09